A remark on positive topological entropy of N-buffer switched flow networks - Xiao-Song Yang (Discrete Dynamics in Nature and Society)
We present a simpler elementary proof on positive topological entropy of the N-buffer switched flow networks based on a new simple theorem on positive topological entropy of continuous map on compact metric space.